The Politics of Consumption and Its Interaction with Sharia Economic Law: Implications and Challenges - Helmi Fitriansyah; Neng Vivie Nurfauziah Rukmini (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
The discussion on the interaction between consumption politics and Islamic Economic Law has become increasingly significant due to growing attention towards halal products, social justice, and economic sustainability. The aim of this research is to analyze the influence of political policies on consumption behavior within the framework of Islamic economics and to identify the implications and challenges of its implementation. The study employs a qualitative approach with descriptive analysis, using data from literature reviews and relevant policies. The findings reveal that consumption politics based on Islamic principles can strengthen social justice, foster the growth of the halal industry, and empower local economies, although challenges remain in terms of monitoring infrastructure, global halal standard harmonization, and consumer literacy. The implication is that effective policies in Islamic consumption politics can promote more inclusive and sustainable economic growth, supported by the synergistic roles of government, businesses, and society.